BRACU new campus development project construction schedule (April.2020-June.2020) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the construction schedule from April, 2020 to June, 2020 of BRACU new campus project.